Production of alternative marine fuels in Brazil: An integrated assessment perspective. (15th March 2021) - Müller-Casseres, Eduardo; Carvalho, Francielle; Nogueira, Tainan; Fonte, Clarissa; Império, Mariana; Poggio, Matheus; Wei, Huang Ken; Portugal-Pereira, Joana; Rochedo, Pedro R.R.; Szklo, Alexandre; Schaeffer, Roberto
Abstract: This study aims to provide an Integrated Assessment Model (IAM) perspective of the production and distribution of alternative marine fuels in Brazilian ports, considering the International Maritime Organization (IMO) emission reduction target for 2050 (IMO2050). Although other mitigation measures are available, it is likely that alternative fuels will be required, implying additional costs and entailing relevant impacts on other energy chains and land use. Hence, the national IAM BLUES model is adapted to represent the relevant part of the international shipping sector. A set of scenarios is developed considering different fuel alternatives, demand assumptions and national mitigation targets. Findings show that taking into account emissions of CO2 only or of all greenhouse gases (GHGs) within the IMO strategy significantly impacts the optimal technological portfolio. Furthermore, achieving the IMO2050 goal without considering a national decarbonization strategy may result in potential spillovers. The intense use of the energy sector could partially compromise the gains obtained by maritime decarbonization or even surpass it. Therefore, only an integrated mitigation strategy would lead to more effective decarbonization of the entire marine supply. Highlights: There is no single optimal portfolio of alternative fuels for shipping. Brazil can fulfil any low-carbon marine fuel strategy. Marine fuels should be part of all national decarbonization strategies. The decarbonization of shipping should be part of Brazil's deep mitigation pathways.